Rewards and pitfalls of turning toward a micro (and away from integrated systems) for acquisitions: The ideal vs. the affordable/ Avantages et inconvénients du microordinateur (en dehors d’ un système intégré) pour les acquisitions. - Campbell, Mary E. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF